2021
DOI: 10.2174/1874944502114010250
|View full text |Cite
|
Sign up to set email alerts
|

Safety Behavior Predictors Related to the Food Safety of Greenhouse Products among the Greenhouse Owners Based on Protection Motivation Theory

Abstract: Objective: The purpose of this study was to determine the safety behavior predictors related to the food safety of greenhouse products among the greenhouse owners of Jiroft city based on the Protection Motivation Theory (PMT). Methods: A cross-sectional study was conducted with a descriptive-correlation approach in 2018 on 228 greenhouse owners. A researcher-made questionnaire that included demographic variables, PMT structures, and safety behavior was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The results of this study show the more motivated people are to take preventive measures against risks, the more preventive and protective behavior increases within them. In fact, the motivation to protect is synonymous with the behavioral intention that triggers or continues the protective behavior ( 10 ). In a study conducted by Zaremohzzabieh et al ( 39 ) in Malaysia, the intention to perform behavior was directly related to preventive measures and preparedness of households against earthquakes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study show the more motivated people are to take preventive measures against risks, the more preventive and protective behavior increases within them. In fact, the motivation to protect is synonymous with the behavioral intention that triggers or continues the protective behavior ( 10 ). In a study conducted by Zaremohzzabieh et al ( 39 ) in Malaysia, the intention to perform behavior was directly related to preventive measures and preparedness of households against earthquakes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, perceived self-efficacy and perceived response efficacy should overcome adaptive response costs. Protection motivation is synonymous with the behavioral intention that causes or continues the protective behavior (10). In Wunnava's study, regression results showed self-efficacy and response costs were significant and consistent predictors of disaster recovery planning (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation